2010
DOI: 10.1128/aem.02606-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Monitoring and Isolation of Previously Uncultured Bacterial Strains from the Sheep Rumen

Abstract: To estimate the contribution of uncultured bacterial groups to fiber degradation, we attempted to retrieve both ecological and functional information on uncultured groups in the rumen. Among previously reported uncultured bacteria, fiber-associated groups U2 and U3, belonging to the low-GC Gram-positive bacterial group, were targeted. PCR primers and fluorescence in situ hybridization (FISH) probe targeting 16S rRNA genes or rRNA were designed and used to monitor the distribution of targets. The population siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 46 publications
4
34
0
2
Order By: Relevance
“…The roles of uncultured bacteria in plant fiber digestion have yet to be determined, but recent advances in molecular techniques have improved our understanding of this topic. Research has shown that approximately 77% of fiber-associated community members were uncultured bacteria; two previously uncultured strains were isolated from the sheep rumens and confirmed to degrade hemicellulose in the rumen (Koike et al, 2004(Koike et al, , 2010. The high proportion of uncultured bacteria in TS and GS indicated that these bacteria may be involved in ruminal fiber degradation; however, further research is necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of uncultured bacteria in plant fiber digestion have yet to be determined, but recent advances in molecular techniques have improved our understanding of this topic. Research has shown that approximately 77% of fiber-associated community members were uncultured bacteria; two previously uncultured strains were isolated from the sheep rumens and confirmed to degrade hemicellulose in the rumen (Koike et al, 2004(Koike et al, , 2010. The high proportion of uncultured bacteria in TS and GS indicated that these bacteria may be involved in ruminal fiber degradation; however, further research is necessary to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…The development of cultivation-independent techniques led to a decline in isolation and cultivation studies, and results from 16S ribosomal RNA gene sequencing and metagenomic studies consistently emphasize that the majority of sequences are derived from organisms that are phylogenetically distinct from currently cultivated species Fouts et al, 2012). In recent years, there have been few attempts to systematically bring additional organisms into cultivation; however, recent studies in Japan (Koike et al, 2010;Nyonyo et al, 2013) and New Zealand (Kenters et al, 2011; S.J. Noel et al, unpublished) have successfully increased the number of taxa of rumen bacteria that have cultured representatives.…”
mentioning
confidence: 99%
“…While in recent years there have been periodic reports of novel bacteria isolated from the rumen of domesticated and wild ruminants, there have been few attempts to systematically bring additional organisms into cultivation. Recent studies in Japan (Koike et al, 2010, Nyonyo et al, 2013 and NZ (Kenters et al, 2011, Noel et al, unpublished) have successfully increased the number of taxa of rumen bacteria that have cultured representatives. The rumen methanogenic archaea are poorly represented in culture collections, and work is in progress to isolate and genome sequence additional rumen methanogen cultures.…”
Section: Discussionmentioning
confidence: 99%